Predicting Dental Malformations Using Deep Learning: A Model for Estimating the Risk of Oral and Jaw Malformations - Aljashami, Muayad (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Objective: Early detection of oral and jaw malformations is critical for preventing excessive functional and aesthetic headaches. This study proposes a deep getting to know version to improve diagnostic accuracy and allow customized chance stratification, addressing gaps in conventional cephalometric analysis. Methods: A hybrid architecture combining convolutional neural networks (CNN) for picture feature extraction and bidirectional LSTMs for sequential cephalometric evaluation became evolved. The model integrates demographic records (age, gender) and strategies various imaging modalities (panoramic X-rays, CBCT) from 1,291 patients, augmented with noise reduction and z-rating normalization. Results: The version achieved 93.2% accuracy (AUC: 0.94) at the take a look at set, lowering diagnostic mistakes by 22% as compared to present strategies. Class-unique sensitivity ranged from 87.3% (Crossbite) to 95.1% (Class III malocclusion). Inference speed (18 ms/image) passed 3D U-Net benchmarks by way of 3.4×, demonstrating scientific feasibility. Conclusion: By bridging AI-driven analytics with preventive dentistry, this framework complements early malformation detection and supports customized treatment making plans. Its deployment could lessen lengthy-term healthcare expenses and enhance patient effects thru well timed, statistics-knowledgeable interventions.